THE INFLUENCE OF AGRICULTURAL IMPORTS, FOREIGN INVESTMENTS, AND EXCHANGE VALUE ON INDONESIAN ECONOMIC GROWTH - Farida Cahyaning Ayu Nugraheni; Fitrah Sari Islami (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2024)
Economic growth in Indonesia is shaped by the dynamics of international trade, especially through agricultural imports, foreign direct investment (FDI), and exchange rates. The main goal of this research is to explore how agricultural imports, foreign direct investment (FDI), and exchange rates have influenced economic growth in Indonesia from 1990 to 2020. Data from the years 1990 to 2020 was gathered for this study, focusing on variables such as economic development, sales of agricultural products abroad, purchases of agricultural products from other countries, foreign investment, and currency exchange values. The information was sourced from the World Bank. To evaluate the research hypothesis, an econometric model was constructed utilizing the Error Correction Model (ECM) technique, with calculations performed using E-Views version 10. The findings suggest that agricultural imports, FDI, and exchange rates have a lasting impact on Indonesia's economy, with agricultural commodity imports having a negative impact due to increased pressure on domestic agricultural products that struggle to compete with cheaper imported commodities. Investment and exchange rates have a negative and insignificant effect on economic growth in the short term. Therefore, government policies that limit agricultural imports and maintain exchange rate stability are crucial in supporting sustainable economic growth and protecting the domestic agricultural sector from the negative impacts of international trade.